Evaluation of the relationship between dental anxiety and oral health status of mothers and their children - Ekin Besiroglu-Turgut; Sibel Kayaalti-Yuksek; Müge Bulut (BMC, 2024)
Abstract Background Mothers usually have the primary role in raising children and developing health-related behaviors. This study aims to evaluate the relationship between dental anxiety and oral hygiene status of mothers and children's dental anxiety and gingival health. Methods The study included 305 children, aged 4-12 years, who came to the dentist for the first time and their mothers. All the demographic and oral hygiene information were collected through a questionnaire. The dental anxiety of the mothers and children was assessed using the Modified Dental Anxiety Scale (MDAS) and Venham Picture Test (VPT), respectively. The oral examination of the mother and children was performed, and their PI, GI, and DMFT scores were recorded. Results While the correlation between MDAS and VPT was positive and strong in children aged 8-12, it was positive but weak in the 4-7 age group. A significant relationship was detected between the mother's PI, GI, DMFT, and the child's VPT score. According to the mothers' dental anxiety, there were no statistically significant differences in PI, GI, and dmft values in children aged between 4 to 7. A moderately positive and statistically significant relationship between maternal dental anxiety and children's DMFT was identified in children aged 8-12. Conclusions Children's dental anxiety was significantly influenced by maternal dental anxiety, post-treatment complications experienced by the mother, and the oral health status of the mother. Trial registration Clinical Trials-ID: NCT05563532; Registration Date: 17.09.2022.